Corporate social responsibility: A perspective from Weberian economic sociology - Jann Boeddeling (Universität Witten/Herdecke, Fakultät für Wirtschaftswissenschaft, 2012)
Answering the call for a new theoretical approach to Corporate Social Responsibility (CSR), this paper makes a suggestion from a Weberian perspective. It briefly appraises the existing research on CSR and develops key points of a new approach based on their criticism. Suggesting that CSR is a discourse about the role of the economy in society, it discusses whether a suitable new approach for the analysis of CSR can be found outside of economics and business ethics. It is argued that Max Weber's economic sociology and particularly his concept of ideal interests offer an appropriate framework. This framework is developed from Weber's theoretical writings and demonstrated to be used by him to analyze processes of change in the role of the economy in society. The paper then outlines how an analysis of CSR could be carried out building on an ideal interests-framework. It is suggested that such research would significantly advance the understanding of central, yet under-researched elements of CSR. Finally, I argue that the proposed research has the potential of contributing insights to action theoretical questions of modern economic sociology.
Keywords: 330; Corporate Social Responsibility; economic sociology; role of the economy in society; Max Weber; protestant ethic; ideal interests; theory of action; Corporate Social Responsibility; Wirtschaftssoziologie; Diskursanalyse; Werttheorie; Christliche Soziallehre; Verhaltensökonomik; Theorie